Yield Modeling of Okra (Abelmoschus esculentus L. moench) in Bituminous Soils of Southern Ondo State, Nigeria - Bimpe, Imoukhuede Oladunni; Toyin, Fasinmirin Johnson; Gbenga, Olayanju (International Journal of Environment, Agriculture and Biotechnology, 2023)
This study investigated the growth and yield response of okra (Abelmoschus esculentus L. Moench) in bituminous soils of selected communities (Loda, Lofo and Legbogbo) in Irele, southern Ondo State for two consecutive growing seasons (2020 and 2021). The Legbogbo site, which of very low bitumen, serves as the control. The textural class is sandy loam and the soil is acidic. Some samples of soil were collected from three dug soil profile pit at depths 0-100 cm at an interval of 10 cm and moved to the soil laboratory for the analysis of the chemical concentrations of macro and trace elements. The highest value of the heavy metal was recorded at Loda. More so, the least amount of the bitumen concentration was recorded at Legbogbo site (control) and in some cases at Lofo site. Result from the study showed that there is significant difference (P < 0.05) in the values of the heavy metals among the location at all depths. The results from various locations also showed that the soil depth and location were significant (P < 0.05) in their main effects on the soil heavy metals. It was observed that the heavy metal concentration of soil was lower than the permissible limit, an indication that the concentration of heavy metals of the study areas may not have negatively influenced the growth and yield of okra. All agronomic parameters in all locations during the two seasons of experiment were in the way of Legbogbo>Lofo>Loda. Okra had 0 kg.ha-1 pod yield at the Loda site at both 2020 and 2021 growing seasons, while Legbogbo had the greatest fruit yield for both seasons. Okra yield prediction model was developed using the stepwise regression model and it was observed that Okra yield significantly correlated to potassium (r2 = 0.95) at P < 0.05 and phosphorus (r2 = 0.99) (P < 0.01).